A STUDY ON THE FOOD CONSUMPTION OF THE ADOLESCENTS PATTERN - Seema Gopinathan and Bineetha. S. (Star Research Reach, 2016)
Adolescence is a unique period in the life cycle that presents special challenges and opportunities to the individuals. The phenomenal growth that occurs in adolescence, second only to that in the first year of life, creates nutrient needs that are higher than any other time in the lifecycle and optimal nutrition during this time is a requisite for achieving full growth potential. Adolescence being a transition period when they gradually take over the responsibility for their own eating habits, adequate nutrition may be necessarily ensured by monitoring their food consumption patterns. The study was conceived with the objective of finding out the food consumption pattern of adolescent boys and girls. Hundred adolescents comprising of 50 boys and 50 girls in the age group of 13-18 years selected from the various schools of Kollam district of Kerala using the random sampling technique made up the samples of the study. A validated questionnaire was used for the collection of data. The study revealed that majority of adolescents were non-vegetarians consuming three meals a day. Skipping of meals was noticed among a significant proportion of them with breakfast being the most commonly skipped meal. Consumption of health drinks and soft drinks were noticed among a huge majority of adolescents without gender differences. Prevalence of eating out of their homes were noted among a sizeable segment of adolescents irrespective of their gender. Habit of consumption of snacks were prevalent among considerable proportion of adolescents with boys displaying more of this tendency than girls. Fruits were reported as the most common snack eaten by adolescents of both genders. The factors influencing selection of foods in adolescents varied significantly between boys and girls.